2013
DOI: 10.3329/bjas.v41i2.14101
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Brahman crossbred-breeding bulls based on phenotypic performance

Abstract: A beef breed development project was carried out in the Department of Livestock Services (DLS) in 2009 in selected areas of Bangladesh. Under this project, semen of Brahman bulls were imported from the USA and used to inseminate indigenous cows to produce graded calves. The present study was undertaken to select graded Brahman bulls of the aforesaid project for breeding purpose. Using the data of Brahman grade-1 population, 4 (four) bulls were selected based on external appearance, phenotypic performance and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…However, the average body weight from this study is different from other studies. Haque et al (2012) showed 24 months Brahman cross bull weighted at 222 kg; while Tahuk et al (2017) showed that 24 to 30 months Bali bull weighted at 229 kg. The highest growth occurs at the age of 1 to 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, the average body weight from this study is different from other studies. Haque et al (2012) showed 24 months Brahman cross bull weighted at 222 kg; while Tahuk et al (2017) showed that 24 to 30 months Bali bull weighted at 229 kg. The highest growth occurs at the age of 1 to 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Wagyu cattle have the goal of breeding to produce high-fat meat, especially the marbling (Gotoh et al, 2014). Whereas the Brahman Cross cattle, in contrast to the two previous cattle breeds that were characteristic of Taurin cattle, the Brahman Cross was selected towards its resistance to rough climate, poor grazing and more resistant to parasites and disease (Haque et al, 2011). A similar pattern of data was also shown in birth weight (Table 2), Wagyu Bull Cross cattle had the smallest performance (P<0.01) compared to the other two crossbred cattle.…”
Section: Resultsmentioning
confidence: 56%
“…A beef breed development project has been carried out in the Department of Livestock Services (DLS) in 2009 in selected areas of Bangladesh. Under this project, semen of Brahma bulls was imported from the USA and used to inseminate indigenous cows to produce graded calves (Haque et al, 2013). Although there are some high yielding dairy breed of cattle, there is limited number of high yielding meat producing breeds in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…But there is limited study on this breed in Bangladesh. Recently, Haque et al (2013) conducted a study to compare the growth of 25% and 50% Brahma breed in Bangladesh, however there is no such study on disease resistance of this breed in our native climate. Beef production is the result of a combination of both genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%